2009
DOI: 10.1016/j.drugalcdep.2009.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil for the treatment of cocaine dependence

Abstract: Aim Modafinil was tested for efficacy in facilitating abstinence in cocaine-dependent patients, compared to placebo. Methods This was a double-blind placebo-controlled study, with 12 weeks of treatment and a 4-week follow-up. Six outpatient substance abuse treatment clinics participated in the study. There were 210 treatment-seekers randomized, having a diagnosis of cocaine dependence; 72 participants were randomized to placebo, 69 to modafinil 200 mg, and 69 to modafinil 400 mg, taken once daily on awakenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
168
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(176 citation statements)
references
References 25 publications
3
168
5
Order By: Relevance
“…It is this potentiation of neurotransmission that is understood to be responsible for cocaine's psychomotor stimulant effects (e.g., Johanson and Fischman, 1989). Brain dopamine transporters have been implicated in these effects to a (2) Mansbach and Balster, 1993 (+) Rush et al, 2010 (+) Grabowski et al, 2001 (+) Negus, 2003 (+) Shearer et al, 2003 (+) Negus and Mello, 2003a (+) Schmitz et al, 2012 (+) Negus and Mello, 2003b (+) Levin et al, 2015 (2) Barrett et al, 2004 (+) Chiodo et al, 2008 (+) Czoty et al, 2010 (+) Czoty et al, 2011 (+) Banks et al, 2013 (2) Thomsen et al, 2013 (acute) (+) Thomsen et al, 2013 (chronic) (+) Banks et al, 2015 Methylphenidate (2) Hiranita et al, 2009 (+) Collins et al, 2006 (2) Grabowski et al, 1997 (2) Czoty et al, 2013 (+) Schubiner et al, 2002 (2) Levin et al, 2007 Modafinil (+) Newman et al, 2010 (+) Hart et al, 2008 (+) Dackis et al, 2005 (2) Verrico et al, 2014 (2) Anderson et al, 2009 (2) Dackis et al, 2012 (2) Schmitz et al, 2012 (2) Schmitz et al, 2014 (+) Kampman et al, 2015 (2) Karila et al, 2016 Desipramine (2) Mello et al, 1990a (2) Fischman et al, 1990 (+) Gawin et al, 1989 (2) Campbell et...…”
Section: B Pharmacology Of Cocainementioning
confidence: 99%
See 1 more Smart Citation
“…It is this potentiation of neurotransmission that is understood to be responsible for cocaine's psychomotor stimulant effects (e.g., Johanson and Fischman, 1989). Brain dopamine transporters have been implicated in these effects to a (2) Mansbach and Balster, 1993 (+) Rush et al, 2010 (+) Grabowski et al, 2001 (+) Negus, 2003 (+) Shearer et al, 2003 (+) Negus and Mello, 2003a (+) Schmitz et al, 2012 (+) Negus and Mello, 2003b (+) Levin et al, 2015 (2) Barrett et al, 2004 (+) Chiodo et al, 2008 (+) Czoty et al, 2010 (+) Czoty et al, 2011 (+) Banks et al, 2013 (2) Thomsen et al, 2013 (acute) (+) Thomsen et al, 2013 (chronic) (+) Banks et al, 2015 Methylphenidate (2) Hiranita et al, 2009 (+) Collins et al, 2006 (2) Grabowski et al, 1997 (2) Czoty et al, 2013 (+) Schubiner et al, 2002 (2) Levin et al, 2007 Modafinil (+) Newman et al, 2010 (+) Hart et al, 2008 (+) Dackis et al, 2005 (2) Verrico et al, 2014 (2) Anderson et al, 2009 (2) Dackis et al, 2012 (2) Schmitz et al, 2012 (2) Schmitz et al, 2014 (+) Kampman et al, 2015 (2) Karila et al, 2016 Desipramine (2) Mello et al, 1990a (2) Fischman et al, 1990 (+) Gawin et al, 1989 (2) Campbell et...…”
Section: B Pharmacology Of Cocainementioning
confidence: 99%
“…Seven double-blind, placebo-controlled, randomized clinical trials have investigated modafinil for managing cocaine dependence (Dackis et al, 2005(Dackis et al, , 2012Anderson et al, 2009;Schmitz et al, 2012Schmitz et al, , 2014Kampman et al, 2015;Karila et al, 2016). In the earliest trial (Dackis et al, 2005), cocaine-dependent subjects were randomly assigned to receive 400 mg modafinil per day (n = 30) or placebo (n = 32) for 8 weeks.…”
Section: Putative Medications Assessed In the Animal And Human Lmentioning
confidence: 99%
“…Results from these trials have sometimes shown a positive effect of modafi nil on stimulant abstinence, but the results have been variable (see Anderson et al, 2009;Heinzerling et al, 2010;McGaugh et al, 2009;Shearer et al, 2009). In particular, moderator variables may play a role in the success of treatment.…”
mentioning
confidence: 99%
“…No significant adverse effects were noted. The therapeutic effects of modafinil in cocaine users have been supported by a recently completed multi-site, placebo-controlled clinical trial involving 210 cocaine-dependent outpatients (Anderson et al, 2009). Currently, more than 10 additional clinical trials are under way to further evaluate the efficacy of modafinil treatment for cocaine addiction ( Table 1).…”
Section: Modafinilmentioning
confidence: 99%